Sosialisasi Literasi Pembiayaan Perbankan Syariah di Jenangan Kabupaten Ponorogo - Rizki Listyono Putro; Titi Rapini; Umi Farida (Jurnal Pengabdian Manajemen, 2023)
The implementation of the service aims to provide Islamic banking literacy related to regulations, systems and products from Islamic banking. The implementation of this activity uses the lecture method, implements and discussion sessions. The implementation of community service applies three sessions, namely session one, exposure to community service activities, session two exposure to entrepreneurship and session three exposure to material on Islamic banking financing. Community service was carried out at Jenanagan, Ponorogo Regency in collaboration with BMT Surya Abadi Jangan. The result of this community service activity is that literacy socialization activities have an impact on increasing sharia financial and banking education. The service participants fully understand and understand regulations, systems and various savings products, financing and services in Islamic banking. These findings show the importance of more intensive socialization in order to increase banking literacy in a complex society.